2015
DOI: 10.1186/s12943-015-0459-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 7 sensitizes O6-methylguanine methyltransferase expressing-glioblastoma stem cells to clinically relevant dose of temozolomide

Abstract: BackgroundTemozolomide (TMZ) is an oral DNA-alkylating agent used for treating patients with glioblastoma. However, therapeutic benefits of TMZ can be compromised by the expression of O6-methylguanine methyltransferase (MGMT) in tumor tissue. Here we used MGMT-expressing glioblastoma stem cells (GSC) lines as a model for investigating the molecular mechanism underlying TMZ resistance, while aiming to explore a new treatment strategy designed to possibly overcome resistance to the clinically relevant dose of TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 72 publications
0
49
0
Order By: Relevance
“…To thoroughly explore the potential prognostic biomarkers for glioma, kinome‐wide hierarchical bi‐clustering was performed using previously published microarray databases related to TMZ resistance, World Health Organization (WHO) grade, and radiotherapeutic resistance (Tso et al, 2015; Mao et al, 2015 and Wang et al, 2017). The differentially expressed genes were sorted by their fold changes (Figure A‐C, and Tables S1‐S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To thoroughly explore the potential prognostic biomarkers for glioma, kinome‐wide hierarchical bi‐clustering was performed using previously published microarray databases related to TMZ resistance, World Health Organization (WHO) grade, and radiotherapeutic resistance (Tso et al, 2015; Mao et al, 2015 and Wang et al, 2017). The differentially expressed genes were sorted by their fold changes (Figure A‐C, and Tables S1‐S3).…”
Section: Resultsmentioning
confidence: 99%
“…A, Kinome‐wide microarray analysis for 668 kinase‐encoding genes in GBM neurosphere compared with the nontumor (Mao et al, 2015). B, Kinome‐wide microarray analysis for 668 kinase‐encoding genes in TMZ‐resistant glioma cell lines compared with the nontreated cells (Tso et al, 2015). C, Kinome‐wide microarray analysis for 668 kinase‐encoding genes in radiation‐treated glioma cell lines (IR) compared with the nontreated cells (Wang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some investigators observe that GSCs give rise to endothelial cells (ECs)60, as shown in Figure 1, and induce changes in vascular niches, characterized by the sprouting of new blood vessels, consisting of an abundant, leaky and highly disorganized "glomeruloid" vascular network through the cooperative secretion of pro-angiogenic factors [1,61,67], such as VEGF, IL-8 and YKL-40 [2,29,56], highly different in patients with the same tumor [42,56,60,82]. YKL-40, also known as chitinase-like protein 1 or human cartilage glycoprotein-39 [6], is a highly conserved glycoprotein that belongs to the glycosyl hydrolase family 18 with no chitinolytic activity [7,84], included as a mesenchymal marker overexpressed in GB and postulated as one of the most promising predictive serum markers since it was found to have elevated levels in the serum of patients with GB [6,29,31,32,35].…”
Section: Glioblastoma Stem Cells and Ykl-40mentioning
confidence: 99%
“…5 The BMP family of growth factors has been proposed as potential non-cytotoxic therapeutic agents for inhibiting the growth of GIC by inducing differentiation 6 and sensitization to temozolomide. 7 BMP signaling promotes the differentiation of GIC by BMP type I receptors and the intracellular signaling pathway. 8,9 Moreover, our previous study showed that BMP-4 and BMP-7 induce apoptosis by activating the BMP type I receptor ALK-2.…”
mentioning
confidence: 99%